The MARKETING MIX EFFECTIVENESS ON INDOMARET'S CONSUMER PURCHASE DECISION: Marketing Mix - Arum Wahyuni Purbohastuti (Sains Manajemen : Jurnal Manajemen UNSERA, 2021)
At present, many retail businesses are closing their businesses because many competitors are developing new technologies. So that researchers are interested in examining the marketing mix conducted by Indomaret in impoving purchasing decisions. The purpose of this study is to examine the marketing mix (product, price, place and promotion) on purchasing decisions. Samples taken in this study amounted to 30 people with pusposive sampling technique. This study uses multiple regression. The result of this study, the product and place have a positive effect on purchasing decisions. While prices and promotions do not have a positive effect on purchasing decisions. Keywords : Prduct, Price, Place, Promotion, and purchasing decisions.